Combined vascular malformation and retention cyst in the maxillary sinus - Almeida, Adriana Ávila de [UNESP]; Almeida, Sérgio Abreu de; Guimarães Filho, Rubens; Anbinder, Ana Lia [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Almeida, Janete Dias [UNESP] (Elsevier, 2017)
Objectives Retention cysts are common in the maxillary sinuses. Combined vascular malformations are abnormalities that involve at least two types of vessels and are frequent in different regions of the organism, especially the skin. The association of a combined vascular malformation and retention cyst in the maxillary sinus is rare. We report the case of a 35-year-old asymptomatic male patient in whom a maxillary sinus cyst was detected during orthognathic surgery. The histopathological findings were compatible with a combined capillary and lymphatic malformation associated to a retention cyst. Methods Case report of a combined vascular malformation in a maxillary sinus retention cyst. Results Histopathological analysis revealed findings compatible with a combined vascular and lymphatic malformation and a retention cyst lined with ciliated pseudostratified respiratory epithelium. Numerous dilated blood and lymphatic vessels, delimited by a single layer of endothelial cells, were observed near the cyst. Immunohistochemistry for D2-40 antigen was positive in the lining cells of lymphatic vessels and CD34 was detected in endothelial cells of capillary blood vessels. Conclusion To our knowledge, this is the first case of the association of a combined capillary and lymphatic malformation and retention cyst in the maxillary sinus. Vascular malformations should be included in the diagnostic hypotheses for cystic lesions of the maxillary sinus usually considered retention cysts. It is possible that other cases of combined vascular malformations exist. In this way, it is important to emphasize the need of histopathological examination of all specimen removed during maxillofacial surgeries.
Keywords: Combined vascular malformations; Maxillary sinus; Retention cyst